Business skills empowerment program through incubation and mentorship for selected pig agripreneurs in Masaka and Mukono districts: process, outcomes and lessons - Kamau, Loise; Tugume, Grace; Ahumuza, Ronnie; Marshall, Karen; Ouma, Emily A. (International Livestock Research Institute, 2024)
The agripreneur business incubation/acceleration program, started in 2023 in Uganda to address challenges associated with market inefficiencies including weak linkages between pig farmers, pig aggregators and input and service providers; poor business practices by artificial insemination (AI) technicians/animal health service providers and limited networks to enable optimal business operations.